A BIBLIOMETRIC ANALYSIS OF SELF-EFFICACY IN STUDENT LEARNING ENGAGEMENT FROM 2014 TO 2023 - Ceceng Saepulmilah; Septian Cahya Azhari (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2023)
Self-efficacy is recognized as a crucial factor in student learning engagement. In several recent studies on student learning engagement, self-efficacy has shown a positive relationship with it, indicating significant research interest in self-efficacy. Additionally, there has yet to be a bibliometric analysis of self-efficacy and student learning engagement in the past decade. This study aims to conduct a bibliometric analysis and explore the current research landscape on self-efficacy from 2014 to 2023. The research database used for this study is from dimensions.ai. VosViewer is employed for bibliometric analysis and scientific mapping of publications, countries, journals, authors, and terms and keywords. Ninety countries have produced at least five documents each in this research field, with the USA leading in the highest number of publications, followed by China in the second position. Among journals, Nurse Education Today (n = 2890) has the highest citation rate, followed by Frontiers in Psychology (n = 2512). Key terms in research on self-efficacy and student learning engagement include motivation, engagement, anxiety, academic performance, university student, academic efficacy, burnout, student engagement, life satisfaction, academic procrastination, and teacher support. The literature volume on self-efficacy has experienced growth over the past ten years and is expected to continue to increase. The field of study has also become more refined. This bibliometric analysis provides substantial support for understanding the evolving trends in self-efficacy and student engagement research.